Preparation of Porous Mo(VI)-Imprinted Algae for Recognizing Molybdenum(VI). Issue 5 (19th September 2021) - Wang, Yuejiao; Yang, Kun; Wang, Jing; Yu, Haibiao; Cui, Junshuo; Xiong, Ying
ABSTRACT: In this article, a novel Mo(VI)-imprinted adsorbent based on brown algae (Mo-PVA-SA-I) was synthesized through an ion-imprinting technique in combination with surface imprinting and polymer crosslinking. As the template ion, H3 Mo7 O24 3 – also acts as the cross-linker to effectively decrease the space and distance between the molecular chains and make the algae form a uniform size of porous structure, it can be used to construct Mo(VI)-matching specific "cavities" after being eluted. Results indicated that the Mo(VI)-imprinted algae have a poor adsorption capacity for its coexisting ions, such as rhenium, copper, iron, zinc, and manganese metal ions at pH 3, while it exhibits apparently higher selective recognition ability for Mo(VI) than the non-imprinted absorbent (Mo-PVA-SA-N). In addition, the prepared Mo(VI)-imprinting algae was equipped with a high adsorption capacity of 114.40 mg·g –1 for Mo(VI). The excellent adsorption performance of this novel Mo-PVA-SA-I adsorbent has been proven to be due to electrostatic attraction between the C = N + –H imine groups and H3 Mo7 O24 3 – in the "cavities" by both FT-IR and XPS analysis. As a result, this novel and environment-friendly Mo(VI)-imprinted algae will be a promising candidate for recovering Mo(VI) from industrial wastewater.